(untitled) (LINGUISTIK TERAPAN, 2023)
In the current digital era, memes are rapidly gaining popularity and transforming into a form of communication through numerous social media platforms. Education field has also been impacted by the rise of memes. This study investigated the macrostructure dimension of education memes in the lens of Van Dijk critical discourse analysis framework. The purpose of this study is to examine the dimension of macrostructure on education memes. In this study, descriptive qualitative research was used. The data sources included four Instagram groups, namely Itb.receh, school_life memories, 9gag.com, and memeindonesia.real. There were a total of 40 chosen education memes. Documentation was utilized to collect the data. Additionally, Van Dijk Critical Discourse Analysis Framework was used to analyze the data. The findings showed that five topics emerged in the selected education memes, namely portrait of students™ problem, teacher professionalism, school infrastructure, language learning and reality of school education. The topic of portrait of students™ problems is the most dominant one. 25 education memes or 62.5% express students™ problems while the least dominant topic is school infrastructure which specifically discussed about bad condition of school toilet.